Ứng dụng chỉ số hài lòng khách hàng của Mỹ - Một nghiên cứu trong lĩnh vực dịch vụ viễn thông di động tại Việt Nam - Nguyễn Văn , Anh; Nguyễn Thị Phương , Thảo (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
This study aims to find out customer satisfaction in the field of mobile phone services in Vietnam through the application of American Customer Satisfaction Index (ACSI) model. Quantitative research applies PLS-SEM analysis technique with a set of data collected through structured questionnaires with 225 mobile phone users. The results show that the ACSI model is suitable in the field of mobile services in Vietnam market. In addition, customer expectations, perceived quality, and perceived value are important factors impacting customer satisfaction and loyalty ultimately. Moreover, customer satisfaction also affects the complaint, and the subsequent complaint will reduce the loyalty of customers using mobile services in Vietnam. The study shows the possibility to form the Vietnamese Customer Satisfaction Index in the near future.
Keywords: Vietnam; ACSI; Mobile phone service; Loyalty; Satisfaction